The Septuagint as a holy text – The first ‘bible’ of the early church - Johann Cook (HTS Teologiese Studies/Theological Studies, 2020)
This article acknowledges the fact that historically there are two phases in the emergence of the Septuagint – a Jewish phase and a Christian one. The article deals first with methodological issues. It then offers a historical orientation. In the past some scholars have failed to distinguish between key historical phases: the pre-exilic/exilic (Israelite – 10 tribes), the exilic (the Babylonian exile ‒ 2 tribes) and the post-exilic (Judaean/Jewish). Many scholars are unaware of the full significance of the Hellenistic era, including the Seleucid and Ptolemaic eras and their impact on ‘biblical’ textual material. Others again overestimate the significance of this era; the Greek scholar Evangelia Dafni is an example. Many are uninformed about the Persian era, which includes the Achaemenid, Parthian and Sassanian eras, each one of which had an impact on Judaism. An example is the impact of Persian dualism. Another problem is the application of the concept of ‘the Bible’. The notion of ‘Bible’ applies only after the 16th century Common Era, specifically after the advent of the printing press. Earlier, depending on the context, we had clay tablets (Mesopotamia), vella (Levant-Judah) and papyri (Egypt) to write on. This is followed by a discussion of the Masoretic text and the LXX, including the reasons for the rejection of the LXX by the Jews. This is significant because the LXX was originally a Jewish document. Attempts to re-evaluate the concept of the Bible are discussed. The Septuagint subsequently followed, which leads to the conclusion that the LXX became the first Bible of the Christian church.